Quantifying the Effects of the CNB's Exchange Rate Commitment: A Synthetic Control Method Approach - Matej Opatrny (Charles University in Prague, Institute of Economic Studies (IES), 2016)
In this paper I evaluate the quantitative effects of the Czech National Bank's commitment to keep the Koruna from appreciating that were put in place in 2013. I focus its on the impact on output, unemployment, and inflation. I use the synthetic control method, which allows me to compute the counter-factual development of the Czech economy in the absence of the commitment. I find that, until the end of 2015, the commitment helped create about 100,000 jobs. The effect on overall output is also strongly positive, almost 2% for growth in 2015, but only marginally statistically significant, which might be connected to disturbances created by changes in excise taxes. The effect of the commitment on inflation is positive but not statistically significant at standard levels.
Keywords: E42; E47; E50; E51; E52; E58; 330; inflation; unemployment; output; currency; monetary policy; synthetic control method